Tailored Fiber Alignment in Holed Bamboo Fiber Reinforced Plates - Korayem, Abd-Elrahman; Kepreos, Alex; Haq, Mahmood (Journal of Fibers and Polymer Composites, 2025)
Natural fiber composites have proven elusive to large scale use in industry due to their lower mechanical properties than glass or carbon fibers despite their low cost, natural availability, and sustainable sourcing. A method to overcome this obstacle is by placing the fibers in the optimum orientation to best resist the stresses the component is subjected to. This is achieved through a simple analysis of the part’s stress distribution and then using the Tailor Fiber Placement (TFP) process to orient the fibers to optimally resist these stresses. In this study holed Bamboo-Polyester Composite Plates (BPCP) were made using Vacuum Assisted Resin Transfer Molding (VARTM), compression molding and TFP processes. Different fiber orientations and crack resistance patterns were devised to compare the performance of the natural fibers to drilled Fiber Glass Chopped Strand Matts (FGCSM). The study showed that for a tensile test of a rectangular composite plate with a fiber content of 25% Volume, the holed BPCP exhibited a 65 MPa tensile strength and 1.75% strain, which is 172% and 145% of that of a comparable drilled FGCSM plate with the same fiber volume fraction respectively.